2021
DOI: 10.3390/molecules26185457
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Screening Approaches for Profiling of Volatile Organic Compounds Based on Gas Chromatography-Ion Mobility Spectroscopy (GC-IMS) and Machine Learning

Abstract: Due to its high sensitivity and resolving power, gas chromatography-ion mobility spectrometry (GC-IMS) is a powerful technique for the separation and sensitive detection of volatile organic compounds. It is a robust and easy-to-handle technique, which has recently gained attention for non-targeted screening (NTS) approaches. In this article, the general working principles of GC-IMS are presented. Next, the workflow for NTS using GC-IMS is described, including data acquisition, data processing and model buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 141 publications
(245 reference statements)
0
17
0
Order By: Relevance
“…Our artificial upsampling and learning pipeline that makes it possible to train machine learning algorithms on a few samples of SPME-DART-MS data, with high precision. Most previous work [ 30 , 31 , 32 , 33 ] rely on an intermediate step of peak detection and identification of VOCs using the NIST05 mass spectral library. In our work, an end-to-end pipeline is developed using python, which takes the raw MS data as input and automatically performs background subtraction, peak detection, feature identification, and classification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our artificial upsampling and learning pipeline that makes it possible to train machine learning algorithms on a few samples of SPME-DART-MS data, with high precision. Most previous work [ 30 , 31 , 32 , 33 ] rely on an intermediate step of peak detection and identification of VOCs using the NIST05 mass spectral library. In our work, an end-to-end pipeline is developed using python, which takes the raw MS data as input and automatically performs background subtraction, peak detection, feature identification, and classification.…”
Section: Resultsmentioning
confidence: 99%
“…show that supervised learning can be successfully used to classify microbial strains using meta-information about their VOC profiles [ 30 ]. Other works add to this by showing that SPME and gas chromatography mass spectrometry can be used to sample VOC signatures, which can be used to create VOC profiles for classification [ 31 , 32 , 33 ]. In this work, we use signal processing and ML techniques to develop a rapid, robust and end-to-end Python pipeline for classifying a pathogen as bacteria or fungi, using the raw MS spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, based on the NIST database search, this technology can realize the discovery of trace volatile components in complex sample systems [ 34 ]. HS-GC-IMS is a powerful technique for the separation and sensitive detection of VOCs, with the advantages of high sensitivity and resolution [ 35 ]. In the present study, the VOCs of SS were investigated by HS-GC-IMS and HS-SPME-GC-MS. As can be seen from Table 1 and Table 2 , most volatile organics detected by HS-GC-IMS are small molecular compounds, whereas the detection range of HS-SPME-GC-MS is usually medium molecular weight VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…This gives us a new idea to distinguish Chinese herbal medicines in different regions. A number of studies have indicated that HS-GC-IMS has the capacity to confirm geographical and botanical origin [ 35 ]. For example, HS-GC-IMS was successfully used for reliable classification of geographical origins for both olive oil (EVOO) [ 38 ] and wine [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation